Модели и метод определения состояния организма сотрудника предприятия - Евланов, М. В.; Сердюк, Н. Н. (НТУ "ХПИ", 2015)
Рассмотрены особенности информационных систем управления безопасностью труда на предриятии, недостатки существующих моделей функциональных задач анализа и прогноза изменения состояния сотрудника предприятия, предложены модели и метод, позволяющие описать архитектурные особенности определения функции, которая используется для описания состояния наблюдаемого сотрудника предприятия в конкретный момент времени.

The features of information systems were considered for management by safety of labor on an enterprise, shortcomings of existent models of functional tasks of analysis and prognosis of change of the state of employee of enterprise, are offered models and method which allowing to describe the architectural features of determination of function which is used for description of the state of the employee of enterprise observed in the concrete moment of time. The models and methods of Naive Bayes using allows us to observe the state enterprise employee at a time with using a minimum set of tools diagnostic This greatly simplifies control of the operation during the exploitation of the information system by safety of labor management in the enterprise.
Models and method of determination of the state of organism of employee of enterprise
Keywords: управление безопасностью труда; информационные системы; вредные производственные факторы; классификация состояния сотрудника; метод Naive Bayes; management by safety of labor; harmful production factors; classification of the state of employee; Naive Bayes method